(untitled) (Eurasian Scientific Herald, 2023)
This article presents the synthesis and properties of copolymers based on vinylmorpholine, acrylic acid and colloidal silica as well as the dependence of the number of monomers on the molecular weight in the copolymerization reaction of vinylmorpholine and acrylic acid